Sex-specific pleiotropic changes in emotional behavior and alcohol consumption in human α-synuclein A53T transgenic mice during early adulthood - Kalinichenko, Liubov; Kohl, Zacharias; Mühle, Christiane; Hassan, Zurina; Hahn, Agnes; Schmitt, Eva-Maria; Macht, Kilian; Stoyanov, Lyubomir; Moghaddami Fara, Schayan; Bilbao, Roberto; Eulenburg, Volker; Winkler, Jürgen; et al. (Journal of neurochemistry, 2024)
Point mutations in the α-synuclein coding gene may lead to the development of Parkinson's disease (PD). PD is often accompanied by other psychiatric conditions, such as anxiety, depression, and drug use disorders, which typically emerge in adulthood. Some of these point mutations, such as SNCA and A30T, have been linked to behavioral effects that are not commonly associated with PD, especially regarding alcohol consumption patterns. In this study, we investigated whether the familial PD point mutation A53T is associated with changes in alcohol consumption behavior and emotional states at ages not yet characterized by α-synuclein accumulation. The affective and alcohol-drinking phenotypes remained unaltered in female PDGF-hA53T-synuclein-transgenic (A53T) mice during both early and late adulthood. Brain region-specific activation of ceramide-producing enzymes, acid sphingomyelinase (ASM), and neutral sphingomyelinase (NSM), known for their neuroprotective properties, was observed during early adulthood but not in late adulthood. In males, the A53T mutation was linked to a reduction in alcohol consumption in both early and late adulthood. However, male A53T mice displayed increased anxiety- and depression-like behaviors during both early and late adulthood. Enhanced ASM activity in the dorsal mesencephalon and ventral hippocampus may potentially contribute to these adverse behavioral effects of the mutation in males during late adulthood. In summary, the A53T gene mutation was associated with diverse changes in emotional states and alcohol consumption behavior long before the onset of PD, and these effects varied by sex. These alterations in behavior may be linked to changes in brain ceramide metabolism.
Gesehen am 27.11.2024